2007
DOI: 10.1073/pnas.0700959104
|View full text |Cite
|
Sign up to set email alerts
|

Transient 2D IR spectroscopy of ubiquitin unfolding dynamics

Abstract: Transient two-dimensional infrared (2D IR) spectroscopy is used as a probe of protein unfolding dynamics in a direct comparison of fast unfolding experiments with molecular dynamics simulations. In the experiments, the unfolding of ubiquitin is initiated by a laser temperature jump, and protein structural evolution from nanoseconds to milliseconds is probed using amide I 2D IR spectroscopy. The temperature jump prepares a subensemble near the unfolding transition state, leading to quasi-barrierless unfolding (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
181
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(190 citation statements)
references
References 51 publications
6
181
0
3
Order By: Relevance
“…7,8 Other important ways to increase effective resolution of the optical spectra include site-specific labeling with stable isotopes 9 and twodimensional multiphoton spectra sampling the chromophore coupling. 10 Simulations by modern quantum-chemical methods represent powerful tools for the spectra interpretations. 7,11,12 By comparison of the computed and experimental Raman and ROA spectral shapes not only the equilibrium structure but also an important knowledge about molecular flexibility and multiconformational states could be acquired.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Other important ways to increase effective resolution of the optical spectra include site-specific labeling with stable isotopes 9 and twodimensional multiphoton spectra sampling the chromophore coupling. 10 Simulations by modern quantum-chemical methods represent powerful tools for the spectra interpretations. 7,11,12 By comparison of the computed and experimental Raman and ROA spectral shapes not only the equilibrium structure but also an important knowledge about molecular flexibility and multiconformational states could be acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions a quantitative analysis of the spectra-structure relationships can be obtained. The 2D IR spectra of amyloid fibrils with 13 CA 18 O substitutions exhibit novel manifestations of the extended 3D structure of the fibrils, including the spatial arrangement of the coupled amide units and the presence of both static and fluctuating electric fields.…”
Section: A Myloid Fibrils Are Found In the Brain Tissue Of Persons Withmentioning
confidence: 99%
“…There has been a considerable amount of experimental work relating the 2D IR spectra of small peptide aggregates to their structure (13)(14)(15)(16)(17), and the recent experimental and theoretical applications of 2D IR have involved macromolecular systems such as folding proteins (18) and fibrils (19,20).…”
Section: A Myloid Fibrils Are Found In the Brain Tissue Of Persons Withmentioning
confidence: 99%
“…The 2DIR technique distinguishes β-sheet structures by producing Z shape like spectra [18,19] when this particular structural motif is present. In the past decades a number of 2DIR studies have been reported of peptides and proteins in solution [16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] or confined in membranes [34][35][36][37][38], revealing structural details and conformational changes from femtosecond (fs) to nanosecond (ns) time scales, and the nature of dynamic environments. For the structure determination of peptides that are in gas phase or micro-solvated (surrounded by few solvent molecules) the mid-infrared spectroscopic technique has become a promising tool [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%